Sistem Pendistribusian Zakat Berbasis Android Dan Web Di Kecamatan Lowokwaru Kota Malang - Novita Lady Wahyuni; Sugeng Widodo (Prosiding SISFOTEK, 2021)
There are many methods that can be used to pay tithe in the current digital era, but there are also many Indonesian people who still believe that zakat is carried out in mosques around their homes. Meanwhile, the data on the distribution of zakat in mosques has not been recorded properly, so there are often errors in the distribution of zakat to mustahik. So this research is intended to create a web application that can make it easier for amil in managing data on zakat received and zakat that has been distributed. The method of analysis and system development uses the prototyping method. Where this system is designed with UML (Uniefied Modeling Language) tools and compiled with HTML, PHP, and Javascript programming languages. In this system, amil can manage and calculate the zakat funds received and facilitate the process of distributing zakat evenly according to the zakat recipient data that has been previously entered in the system by the amil. In addition, this application can be use from anywhere and do not have to come to the destination mosque.This application also provided information about the amount of zakat that has been determined by each mosque.